The role of diet in modulating the intestinal microbiota in healthy adults: Is the evidence enough? - Ruta, Florina; Mardale, Elena; Pintea, Andrada; Avram, Calin (Acta Marisiensis - Seria Medica, 2023)
The diet is an important factor that can influence the structures and function of the population of germs that compose the intestinal microbiota. This review presents current data on the response of the intestinal microbiota depending on the diet. While many studies have shown that the intestinal microbiota is influenced by macronutrient and micronutrient compounds of the diet, the studies on healthy human subjects were fewer and showed only to a small extent the influence of cooked food on the intestinal microbiota. Additional research is still needed regarding the effect of the way food is cooked can have on the intestinal microbiota, before beneficial dietary recommendations can be made.